2008
DOI: 10.1155/2009/515178
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Lead(II) Ions by Adsorption ontoBamboo Dust and Commercial Activated Carbons ‐A Comparative Study

Abstract: Studies on the removal of lead(II) ions by adsorption onto indigenously prepared bamboo dust carbon (BDC) and commercial activated carbon (CAC) have been carried out with an aim to obtain data for treating effluents from metal processing and metal finishing industries. Effect of various process parameters has been investigated by following the batch adsorption technique at 30±1°C. Percentage removal of lead(II) ions increased with the decrease in initial concentration and increased with increase in contact tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(40 citation statements)
references
References 7 publications
3
36
1
Order By: Relevance
“…Adsorption applications of onion skins have been carried out by various assays (Saka et al 2011a, b;Saka and Ş ahin 2011 AbdelGhani et al 2007AbdelGhani et al , 2008Abdel-Ghani and Elchaghaby 2007;Abdel-Halim et al 2003;Ahluwalıa and Goyal 2005;Benhimaa et al 2008;Chamarthy et al 2001;Dahiya et al 2008;El-Ashtoukhya et al 2008;Feng et al 2004;Fıol et al 2006;Ghaffar 2008;Goel et al 2005;Gong et al 2005;Gueu et al 2007;Han et al 2005;Hanafiah et al 2006;Hashem 2007;Ho and Ofomaja 2006;Ho 2005;Ilhan et al 2004;Imamoglu and Tekir 2008;Iyagba and Opete 2009;Kannan and Thambidurai 2007;Kannan and Veemaraj 2009;Kim et al 2006;Kiran and Akar 2005;Krishnan et al 2003;Liao et al 2010;Lugo-Lugo et al 2009;Martınez et al 2006;Meunier et al 2003;Naddafi et al 2007;Ö zdemir et al 2004;Qaiser et al 2009;Quek et al 1998;Sarı and Tuzen 2008;Sekar et al 2004;…”
Section: Onion Skinsmentioning
confidence: 99%
“…Adsorption applications of onion skins have been carried out by various assays (Saka et al 2011a, b;Saka and Ş ahin 2011 AbdelGhani et al 2007AbdelGhani et al , 2008Abdel-Ghani and Elchaghaby 2007;Abdel-Halim et al 2003;Ahluwalıa and Goyal 2005;Benhimaa et al 2008;Chamarthy et al 2001;Dahiya et al 2008;El-Ashtoukhya et al 2008;Feng et al 2004;Fıol et al 2006;Ghaffar 2008;Goel et al 2005;Gong et al 2005;Gueu et al 2007;Han et al 2005;Hanafiah et al 2006;Hashem 2007;Ho and Ofomaja 2006;Ho 2005;Ilhan et al 2004;Imamoglu and Tekir 2008;Iyagba and Opete 2009;Kannan and Thambidurai 2007;Kannan and Veemaraj 2009;Kim et al 2006;Kiran and Akar 2005;Krishnan et al 2003;Liao et al 2010;Lugo-Lugo et al 2009;Martınez et al 2006;Meunier et al 2003;Naddafi et al 2007;Ö zdemir et al 2004;Qaiser et al 2009;Quek et al 1998;Sarı and Tuzen 2008;Sekar et al 2004;…”
Section: Onion Skinsmentioning
confidence: 99%
“…Kalkan E., et al may be chemisorption, which involves valence forces by sharing or electron exchange between the adsorbent and the adsorbate [45,46]. The pseudo-second-order kinetic model is given by the following equation.…”
mentioning
confidence: 99%
“…On the other hand, different kinds of sorbents were studied. In this, hence, areca (a food waste), Iranian natural zeolite, bamboo charcoal, MWCNT, and fly ash, using for heavy metal removal [32][33][34][35], were checked as adsorbent. The obtained results were shown that the time of the proposed method is much shorter (50 min), and the amount of sorbent is significantly lower than other ones (0.001 g), which is indicative of efficiency of CMNTs (Table 3).…”
Section: Kinetic Modeling and Thermodynamic Of Adsorptionmentioning
confidence: 99%